Effect of single and mixed inoculation of arbuscular mycorrhizal fungi and phosphorus fertilizer application on corn growth in calcareous soil - Lily Ishaq; A.S.J. ADU TAE; MORESI A. AIRTHUR; PETERS O. BAKO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ishaq L, Adu Tae ASJ, Airthur MA, Bako PO. 2021. Effect of single and mixed inoculation of arbuscular mycorrhizal fungi and phosphorus fertilizer application on corn growth in calcareous soil. Biodiversitas 22: 1920-1926. Low availability of soil phosphorus (P) in calcareous soil in West Timor has become a constraint in improving plant productivity. A field experiment was carried out in the calcareous soil to investigate the effect of single and mixed indigenous arbuscular mycorrhizal fungi (AMF) inoculation and P fertilizer application on growth and yield of corn in Kupang District, East Nusa Tenggara Timur Province, Indonesia. The experiment was laid out in a split-plot design consisting of indigenous AMF inoculation as the main plots and inorganic P fertilizer rates as the sub-plot treatments. The main plot treatments were: without AMF inoculation (M0), inoculated with single AMF inoculum (M1) and inoculated with mixed AMF inocula (M2). Sub-plots consisted of four P rates namely 25% (P1), 50% (P2), 75% (P3) and 100% (P4) of the recommended inorganic superphosphate dose of 200 kg SP36 ha-1. The results showed that there were significant interactions between AMF inoculation and P fertilizer dose on AMF spore density, AMF colonization and soil available P. Results indicated a strong correlation between AMF colonization and soil available P. Inoculation of both M1 and M2 significantly increased soil available P, plant growth and yield compared to the uninoculated plant. Spore production in the two AM responded differently to P fertilizer. Low doses of inorganic P fertilizer favored spore production in M1, whereas P fertilizer sporulation in M2 was adversely affected. The percentage of AMF root colonization of M1 and M2 decreased with an increase in P fertilizer applied. Further studies need to be conducted to evaluate the effectiveness of indigenous AMF in improving plant yield at low level of inorganic fertilizer application to achieve more sustainable agricultural practice in the region.